2018
DOI: 10.1177/1120672118815107
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic practices and musculoskeletal disorders among ophthalmologists in India: An online appraisal

Abstract: Introduction: Ergonomics in ophthalmology is neither taught during professional training nor does it readily receive consideration or priority in clinical practice. Owing to a high prevalence of musculoskeletal disorders among ophthalmologists, ergonomic awareness, and practices are vital in averting this modern epidemic. Objective: To assess the ergonomic practices and prevalence of self-reported musculoskeletal disorders among ophthalmologists in India. Method: An online survey was conducted among ophthalmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Musculoskeletal disorders have been reported in ophthalmic surgeons, indicating that ergonomic practices are of major importance during surgical training 10 . In this study, ergonomics was assessed using the RULA score, which provides an evaluation of the surgeon’s posture (head, trunk posture, and upper limbs, up to the wrist) while seated 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal disorders have been reported in ophthalmic surgeons, indicating that ergonomic practices are of major importance during surgical training 10 . In this study, ergonomics was assessed using the RULA score, which provides an evaluation of the surgeon’s posture (head, trunk posture, and upper limbs, up to the wrist) while seated 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Kaup et al 2020 found that good ergonomic practices in the clinic and OR, such as stretching, maintaining spine neutrality, and ensuring appropriate chair heights, were associated with fewer MSK symptoms. 7 Perhaps the ideal method to establish the effect of volume metrics on MSK symptoms would be to account for lifetime clinic and surgical numbers, and to define the extent of disability longitudinally. However, this approach would be challenging given recall bias and lack of documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Long periods spent in awkward positions can also contribute. [2] Ophthalmologists frequently have debilitating neck pain, numbness in the hands and legs, carpal tunnel syndrome, and debilitating back pain. When doing routine tasks like a slit lamp examination, using an indirect ophthalmoscope, or even sitting in a surgeon's chair, most work-related problems among ophthalmologists are brought on.…”
Section: Introductionmentioning
confidence: 99%